Effects of Bear Walking and Crocodile Animal Movement Training on Shoulder and Hip Joint Range of Motion in Children Aged 10–12 Years - Bakuh Ikhsa Mahendra Gumilar; Muhammad; I Dewa Made Aryananda (STKIP Pasundan, 2026)
This study aimed to examine the effects of animal movement exercises, namely bear walking and crocodile, on shoulder and hip range of motion (ROM) in children aged 10–12 years. A quasi-experimental pretest–posttest control group design was used. Participants were selected through purposive sampling and assigned to a bear walking group (n=14), crocodile group (n=13), and control group (n=10). ROM was measured using a goniometer and analyzed with paired sample t-tests, Wilcoxon signed-rank tests, and One-Way ANOVA. The results showed significant improvements in shoulder and hip ROM in both exercise groups (p<0.05). Improvements in shoulder ROM were comparable between groups, while the crocodile group showed greater gains in hip ROM than the bear walking group. These findings indicate that animal movement exercises are effective for improving joint mobility in school-aged children.